2019
DOI: 10.1111/jicd.12404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of articaine vs lignocaine in maxillary and mandibular infiltration and block anesthesia in the dental treatments of adults: A systematic review and meta‐analysis

Abstract: Local anesthesia provides the backbone of pain control in dentistry.Local anesthetics give rise to a reversible loss of sensation in a circumscribed area when injected or topically applied, without causing loss of consciousness. Local anesthetics are commonly administered in injectable form in dentistry as a supraperiosteal/infiltration, a field block, or a nerve block. 1 Because of the porous nature of the maxilla, infiltration anesthesia is commonly employed in maxillary injections. The infiltration techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…10 Out of 1022 study participants, Brandt et al 43 found articaine superior to lidocaine for all dental infiltrations and for mandibular block anaesthesia in healthy teeth. 43 Soysa et al 44 found articaine superior to lidocaine for all mandibular interventions. 44 None of the reviews reported any short or long-term paraesthesia.…”
Section: Overview Of Previous Systematic Reviewsmentioning
confidence: 98%
See 3 more Smart Citations
“…10 Out of 1022 study participants, Brandt et al 43 found articaine superior to lidocaine for all dental infiltrations and for mandibular block anaesthesia in healthy teeth. 43 Soysa et al 44 found articaine superior to lidocaine for all mandibular interventions. 44 None of the reviews reported any short or long-term paraesthesia.…”
Section: Overview Of Previous Systematic Reviewsmentioning
confidence: 98%
“…43 Soysa et al 44 found articaine superior to lidocaine for all mandibular interventions. 44 None of the reviews reported any short or long-term paraesthesia.…”
Section: Overview Of Previous Systematic Reviewsmentioning
confidence: 98%
See 2 more Smart Citations
“…Maxillary anesthesia is affected by various factors, the most important being the local anesthetic solution [ 6 7 8 9 ]. Lidocaine has an inherent vasodilatory effect that increases the absorption of the anesthetic solution.…”
Section: Introductionmentioning
confidence: 99%